Simultaneous determination of methylphenidate and ritalinic acid in hair using LC–MS/MS - Jang, Moonhee; Kim, Jihyun; Shin, Ilchung; Kang, Seojin; Choi, Hyeyoung; Yang, Wonkyung (Forensic science international, 2019)
[Display omitted] •An LC–MS/MS method was developed to document methylphenidate use in hair specimens.•Target analytes were methylphenidate and its metabolite, ritalinic acid.•A simple sample preparation was carried out with a small amount of sample.•The method was successfully applied to authentic hair samples from methylphenidate abuse cases. Methylphenidate (MPH) is one of the most commonly prescribed stimulants for attention deficit hyperactivity disorder and its abuse is on the rise with its growing availability. Some analytical methods have been reported for the detection of MPH in hair. However, the concentration range of MPH as well as its metabolite, ritalinic acid (RA) in the hair of MPH abuse cases has not been reported. In this study, a sensitive and reliable liquid chromatography-tandem mass spectrometry method was developed and validated for the simultaneous determination of MPH and RA in hair. Sample preparation was carried out by a simple methanol extraction using 10mg of hair. Limits of detection for MPH and RA in hair were 0.5pg/mg and 1pg/mg, respectively, and the limits of quantification (LOQs) were 1pg/mg for both the analytes. Validation results showed good linearity in the range of 1–100pg/mg with acceptable precision and accuracy. The developed method was applied to real hair samples obtained from ten drug users who obtained MPH illegally without a prescription. MPH concentrations in the hair samples ranged from 1.0pg/mg to 265.0pg/mg, and RA was present at concentrations <LOQ–76.3pg/mg. In this study, hair analysis and background findings revealed that most subjects have abused illicit substances (methamphetamine, Δ9-tetrahydrocannabinol, zolpidem etc.) other than MPH. The low picogram range of LODs for MPH and RA in hair was achieved with the present method and the results from real sample analysis would provide useful information related to MPH abuse under forensic settings.